Immune dysfunction and liver damage of mice following exposure to lanthanoids. Issue 1 (16th September 2011) - Cheng, Jie; Cheng, Zhe; Hu, Renping; Cui, Yaling; Cai, Jingwei; Li, Na; Gui, Suxing; Sang, Xuezi; Sun, Qingqing; Wang, Ling; Hong, Fashui
<x xml:space="preserve">Abstract</x> In an effort to investigate the effects of exposure to lanthanoids (Ln) on the immune response and liver function, mice were orally exposed to LaCl3, CeCl3, and NdCl3 at 2, 10, and 20 mg/kg doses for 30 days, respectively; lymphocyte counts, serum IgM level, hematological indices, biochemical parameters of liver functions, and histopathological changes in Ln3+‐treated mice were assessed. Indeed, 20 mg/kg Ln3+ significantly inhibited mice growth and reduced the counts of white blood cells, platelets, and reticulocyte in mice blood. Specifically, in these Ln3+‐treated mice, CD3+, CD4+, CD8+, CD19+ and NK cells, and CD4+/CD8+ ratio as well as serum IgM level were decreased. Furthermore, liver function was disrupted, as evidenced by the increased alanine aminotransferase, total bilirubin, total bile acid and triglycerides, and the decreased glucose and ratio of albumin to globulin. The cytoarchitecture damage and fatty degeneration in liver caused by Ln3+ at 20 mg/kg dose were also observed. Our findings showed that exposure to Ln affected the cell and humoral immunity and disturbed liver function in mice. In addition, Ce3+ was found to exhibit higher toxicity than La3+ and Nd3+. © 2011 Wiley Periodicals, Inc. Environ Toxicol 29: 64–73, 2014.